PERANCANGAN BUKU CITY GUIDE WISATA CAGAR BUDAYA KOTA SURABAYA MENGGUNAKAN TEKNIK ILUSTRASI PENSIL WARNA GUNA MENINGKATKAN DAYA TARIK WISATAWAN - Sembodo, Kukuh Priyo; Bahruddin, Muhammad; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2016)
The purpose of designing city guide book travel heritage city of Surabaya is to increase the attractiveness of travelers. The study was conducted with qualitative methods of doing interviews, documentation, observation and literature study to get the data used to support the manufacture of the design concept travel guide book heritage city of Surabaya. In the Oxford dictionary of English "Pleasure" has a meaning that is menyenagkan. Description of "Pleasure" in Indonesian big dictionary is made happy or evoke a sense of fun. In such case, this delightful concept that has a relationship with the city of Surabaya traveled heritage that the city guide book travel Surabaya Heritage city can give a pleasant impression for the reader in the guide for Traveling. So in this design to be visualized creatively with an object that looked fun is in illustration of cultural heritage buildings in Surabaya. Results from the design book travel city guide heritage city of Surabaya is to increase the tourist attraction of cultural heritage city of Surabaya. Keywords : Books , City Guides, travel , heritage, Surabaya.